Paysage et interdisciplinarité : regards croisés sur la zone atelier de Pleine-Fougères en Bretagne - Clémence Vannier; Thomas Delattre; Violette Le Féon; Chloé Vasseur; Hugues Boussard (Projets de Paysage)
The « zone Atelier de Pleine-Fougères » meets and confront on one territory researchers from different diciplines who find a common entrance at the landscape level, the product of interactions between nature and society. This concept of landscape can be understood in very different ways of disciplines. To provide a common framework for interdisciplinarity research, we present through phD works of landscape ecology and geography : 1. a common conceptualization of landscape as a “multi-layer” ; 2. area worshop, its research, its landscape and its resources ; 3. through the example of linear elements, how to respond to issues of interdisciplinary research ; 4. the complementarities of different work of the zzne atelier and what make it a real interdisciplinary research tool.